(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2018)
يعد القرار التمويلي من أهم القرارات التي يتم اتخاذها في المؤسسات على اختلاف نشاطاتها الاقتصادية، كونه يتضمن تحديد هيكل التمويل الذي هو مزيج من الديون وحقوق الملكية. ويترتب على هذا القرار العديد من النتائج التي اختلفت باختلاف الإطار النظري الذي تناولها أو الجوانب العملية التي طبقتها.في هذا البحث تم الاعتماد على المنهج الوصفي التحليلي بهدف تسليط الضوء على أهم نظريات هيكل التمويل عالميا انطلاقا من أقدمها وهي نظرية الربح الصافي وصولا الى أحدثها وهي نظرية توقيت السوق. وتحليل أهم الانتقادات الموجهة لها. وتم التوصل الى مجموعة من النتائج أبرزها أنه لا يمكن حتى الآن تعميم نظرية واحدة للهيكل التمويلي وصولا للهيكل التمويلي الأمثل وأن النتائج التي تترتب على تطبيقها تحكمها اعتبارات كثيرة ومحددات مختلفة. The financing decision is one of the most important decisions taken in institutions with different economic activities, it includes determine the financing structure, which is a combination of debt and equity. This decision has many consequences, which differed according to the theoretical framework it research in, or the practical sides it applied. In this research, the descriptive analytical approach was adopted with the aim of the most important theories of the global finance structure were highlighted from the oldest one(the theory of net profit) up to the latest(the theory of market timing). In addition, analyze the most important criticisms. A number of results have been reached, most important that, theory of the financing structure cannot yet possible to generalize a single financing structure theory that reflects the optimal financing structure. Moreover, the consequences of its application were dominated by many considerations and different determinants.